Evaluation of sewerage inflow and infiltration in residential areas within Kuantan, Pahang - Chan, Shiao Ting (2016)
Infiltration rate acts as important aspect in the design of sewerage system. The extraneous water that enters the sewer pipe system through leakage or improper connections will affect the flow rate and flow capacity of wastewater in the sewer pipe. This thesis deals with the inflow and infiltration that is occurring in the current sewerage system and the appropriateness of the sewer pipes design criteria through collection of data from field runs in three different residential areas which are Taman Lepar Hilir Saujana, Bandar Putra and Kota Sas. Besides that, this research also studies the effects of rainfall on inflow and infiltration in the sewerage system, which was found to be large. The data used in this research was obtained by using two area velocity flow-meters to measure the flow rate in the sewers as well as a rain gauge to collect the rainfall data at every location with an average duration of a month per location. This research was done on selected sewer lines connecting two manholes with no lateral branches in between each location. The data obtained was converted into graph form. Thus, inflow and infiltration of the sewerage system and its relationship with rainfall can be clearly seen. The results of inflow and infiltration are compared with the design infiltration rate prescribed in MS1228:1991 and Hammer & Hammer. The highest infiltration rate obtained at Taman Lepar Hilir Saujana (7756.36 liter/day/km/mm-dia); Bandar Putra (9213.53 liter/day/km/mm-dia) are much higher than the design limits mentioned in MS 1228:1991 (50 liter/day/km/mm-dia) and Hammer & Hammer (46 liter/day/km/mm-dia). There was leakage or blockage that occurred at Kota Sas where the infiltration rate was in the negative sign.